Enhanced crystallization kinetics of poly(lactide) with oxalamide compounds as nucleators: effect of spacer length between the oxalamide moieties. Issue 54 (16th May 2016) - Shen, Tianfeng; Xu, Yunsheng; Cai, Xiaoxia; Ma, Piming; Dong, Weifu; Chen, Mingqing
Abstract : Crystallization kinetics of poly (lactide) were enhanced by using oxalamide compounds as nucleators and the nucleation efficiency can be well tailored by tuning the aliphatic spacer length between the oxalamide moieties. Abstract : Poly(lactide), PLA, suffers from low crystallization rate. To speed up the crystallization rate, oxalamide compounds with the formula of C6 H5 NHCOCONH(CH2 ) n NHCOCONHC6 H5 ( n = 2, 4, 6, 8, 12) are synthesized as nucleating agents (NA( n ) ). Their thermal properties and nucleation efficiency can be tailored by tuning the aliphatic spacer length, i.e., –(CH2 ) n –. The melting temperatures and crystallization temperatures of the NA( n ) decrease monotonically with increasing n value while the thermal decomposition temperature remains constant. The aliphatic spacer length ( n ) of NA( n ) influences obviously the crystallization kinetics of PLA, resulting in nucleation efficiency in the sequence of NA(2) > NA(4) > NA(12) ≈ NA(8) > NA(6) . Polarized optical microscopy results show that NA( n ) could self-assemble into needle-like superstructures which subsequently promote the crystallization of PLA macromolecules. The differences in superstructural geometry and the nucleation activity of NA( n ) are responsible for the variation in the nucleation efficiency.